Newborns of mothers with tuberculosis: a series of clinical cases (Archives of Pediatrics of Uruguay, 2020)
Tuberculosis is a serious public health issue in the Americas. Uruguay is no stranger to this reality, and it has shown a steady increase in tuberculosis in the last 10 years, with significant mortality rates as a result of evolved forms of TB and of co-infection with Human Immunodeficiency Virus. This situation has consequences on perinatal health, and the population at highest risk is made up of pregnant women from poor socioeconomic backgrounds, users of psychoactive drugs with HIV co-infection.We hereby present a series of 4 clinical cases of newborns born to women with active tuberculosis at birth from January 2015 to June 2019 assisted at the Pereira Rossell Hospital Center, with an incidence of 0.15 cases for every 1 000 live births. Three of them were carriers of human immunodeficiency virus with a detectable viral load at birth due to poor compliance with the antiretroviral treatment. No resistance to anti-tuberculosis drugs was detected. Regarding newborns, no case of congenital tuberculosis was confirmed. Isolation measures were implemented and first-level tests were performed for the diagnosis of congenital tuberculosis, all of which were negative.
Keywords: Tuberculosis; Vertical infectious disease transmission; HIV infections; Pregnancy; Newborn